Ibrutinib for patients with relapsed or refractory chronic lymphocytic leukaemia with 17p deletion (RESONATE-17): a phase 2, open-label, multicentre study. Issue 10 (October 2016) - O'Brien, Susan; Jones, Jeffrey A; Coutre, Steven E; Mato, Anthony R; Hillmen, Peter; Tam, Constantine; Österborg, Anders; Siddiqi, Tanya; Thirman, Michael J; Furman, Richard R; Ilhan, Osman; Keating, Michael J; et al.
Summary: Background: The TP53 gene, encoding tumour suppressor protein p53, is located on the short arm of chromosome 17 (17p). Patients with 17p deletion (del17p) chronic lymphocytic leukaemia have poor responses and survival after chemoimmunotherapy. We assessed the activity and safety of ibrutinib, an oral covalent inhibitor of Bruton's tyrosine kinase, in relapsed or refractory patients with del17p chronic lymphocytic leukaemia or small lymphocytic lymphoma. Methods: We did a multicentre, international, open-label, single-arm study at 40 sites in the USA, Canada, Europe, Australia, and New Zealand. Patients (age ≥18 years) with previously treated del17p chronic lymphocytic leukaemia or small lymphocytic lymphoma received oral ibrutinib 420 mg once daily until progressive disease or unacceptable toxicity. The primary endpoint was overall response in the all-treated population per International Workshop on Chronic Lymphocytic Leukaemia 2008 response criteria modified for treatment-related lymphocytosis. Preplanned exploratory analyses were progression-free survival, overall survival, sustained haematological improvement, and immunological improvement. Patient enrolment is complete, but follow-up is ongoing. Treatment discontinuation owing to adverse events, unacceptable toxicity, or death were collected as a single combined category. This study is registered withClinicalTrials.gov, numberNCT01744691 . Findings: Between Jan 29, 2013, and June 19, 2013, 145 patients were enrolled. The all-treated population consisted of 144 patients with del17p chronic lymphocytic leukaemia or small lymphocytic lymphoma who received at least one dose of study drug, with a median age of 64 years (IQR 57–72) and a median of two previous treatments (IQR 1–3). At the prespecified primary analysis after a median follow-up of 11·5 months (IQR 11·1–13·8), 92 (64%, 95% CI 56–71) of 144 patients had an overall response according to independent review committee assessment; 119 patients (83%, 95% CI 76–88) had an overall response according to investigator assessment. In an extended analysis with median follow-up of 27·6 months (IQR 14·6–27·7), the investigator-assessed overall response was reported in 120 patients (83%, 95% CI 76–89). 24-month progression-free survival was 63% (95% CI 54–70) and 24-month overall survival was 75% (67–81). Sustained haematological improvement was noted in 72 (79%) of 91 patients with any baseline cytopenia. No clinically relevant changes were noted from baseline to 6 months or 24 months in IgA (median 0·4 g/L at baseline, 0·6 g/L at 6 months, and 0·7 g/L at 24 months), IgG (5·0 g/L, 5·3 g/L, and 4·9 g/L), or IgM (0·3 g/L at each timepoint) concentrations. Common reasons for treatment discontinuation were progressive disease in 34 (24%) patients and adverse events, unacceptable toxicity, or death in 24 (17%) patients. Major bleeding occurred in 13 (9%) patients (11 [8%] grade 3–4). Grade 3 or worse infections occurred in 43 (30%) patients, including pneumonia in 19 (13%) patients. In the extended analysis, 38 patients died, 18 as a result of adverse events (four pneumonia, three chronic lymphocytic leukaemia, two Richter's syndrome, two sepsis, and one each of acute myocardial infarction, septic shock, encephalopathy, general deterioration in physical health, abnormal hepatic function, myocardial infarction, and renal infarction). Interpretation: A high proportion of patients had an overall response to ibrutinib and the risk:benefit profile was favourable, providing further evidence for use of ibrutinib in the most difficult subset of patients with chronic lymphocytic leukaemia or small lymphocytic lymphoma. Ibrutinib represents a clinical advance in the treatment of patients with del17p chronic lymphocytic leukaemia and has been incorporated into treatment algorithms as a primary treatment for these patients. Funding: Pharmacyclics LLC, an AbbVie Company.